Διαδικτυακή διάλεξη/Webinar "Α Museum ‘Top10’: Thoughts on Writing a New Guide Book for the Benaki“ (The Benaki Museum, 2020)
: Ευχαριστώ πάρα πολύ, Νίνο Ευσταθειάδη, και ευχαριστώ πάρα πολύ όλους εσάς. I will now switch to English. Thank you very much, Νίνο Ευσταθειάδη, who is in charge of our members' program and the contemporaries' program. And thank you very much everyone for joining us tonight. This evening we are presenting a lecture sponsored by Bonhams, who have been longtime supporters of the Chinese collection of the Benaki Museum. Will you please allow me now to share my screen, and we can begin proper. Now, the lecture is called a museum top 10 thoughts on writing a new guidebook for the Benaki Museum. And it really is something that is a lecture I've never given before because I have literally just finished yesterday writing the guidebook. And so we thought that we should share with those closest to the museum, the friends for more than 60 years, the members and the contemporaries, our latest group of relatives. And we should share this news and we should discuss the thought process that goes behind a guidebook. Something which we think is quite simple, quite straightforward, but it couldn't be straightforward if it had to do with the Benaki. A guidebook is like a small peephole, a small hole on the wall that gives us access to the treasures lying beyond. And what the author has to do is bore this hole with a drill. It can be very big, it can be much smaller, and let us into this marvelous world of wonders, of miracles. Now the museum in its 90 year old history has had a series of guidebooks. And I'm showing you here the 1935 book written by its first director, Theodoros Makridis, also known as Makridis Bey, because he was an eminent archaeologist in the Ottoman Empire. He had worked with Osman Hamdi Bey, the first director of the Archaeological Museum of Constantinople. And he was hired by Adonis Benakis, the museum's founder, to be the inaugural director. Not many people know of the illustrious career of the Benakis first director. The second book we see is the 1958 guidebook written by Manolis Chatzidakis. I will refer a little bit later to the second director of the museum. And the third was written in 1990 by Angelos Delivorgias, the director most of us have identified with the museum as he was in that place for over 40 years. Angelos Delivorgias authored also the rather monumental volume, Greece at the Benaki Museum, published in 2000, and the smallest but easier to read guide to the Benaki Museum published the same year. In 2006 Anna Balian, Mina Moraitu and Maria Sardi, with an introduction by Delivorgias, published the guidebook to the Benaki Museum of Islamic Art. And there are, of course, other publications, not guidebooks as such, a bit more scholarly, covering the rest of the collections of the museum. When, about two years ago, the museum was approached by an international publishing house, I'm not going to give too many details on that project because it's not finalized yet. And with the request for a new guidebook, the directives were quite strict. What we were given were less than 100 pages. And when you added up how things should be presented, we ended up with less than 40 objects. So the challenge was, should we do a guidebook for each of the Benakis? And for those of you who are not very familiar with the museum structure, I will briefly explain it later, but we do one for the whole museum. How can we possibly identify 40, or actually less than 40, 38 highlights of such a museum? And what are the considerations that should weigh on the mind of anyone attempting this? I would argue that the first consideration is the people that have marked the museum. The people that have made the Benakis what it is. And I roughly, I have separated them in two groups, although I would argue that these two groups are not distinct. First, we have the people that have worked at the museum, either as members of its board or as employees. And of course, we begin with the founder, the original donor, and the original chairman of the museum, Antonis Benakis himself, seen in a rather rare photograph here. And I would juxtapose him with the second director of the museum, Manolis Chatzidakis, an eminent art historian whom Benakis, while he was still a curator at the museum, had helped and had commissioned to study Arab language and Islamic art in Europe. Of course, we know Manolis Chatzidakis as a major Byzantinist, because this was the orientation his research took after he came back to Greece. Another important chairman of the museum was Lambros Eftaxias, also a great benefactor of other charitable institutions, and he reigned supreme in the later sixties and seventies in Athenian cultural life. At the Benakis, he was succeeded by Irini Kaliga, the daughter of the founder, the daughter of Antonis Benakis, who also served as the chair of the museum between 1990 and 1995. And she was followed by her daughter, Marinos Geroulanos, her son-in-law, and by her daughter, Emilia Geroulanos, seen here in the lovely webbing portrait by Yanis Moralis. Last but definitely not least, I couldn't but mention Angelos Delivoglias, the legendary director of the museum, in office between 1973 and 2014. So these were the people that were at the museum every day while they were in office, and even after that, as we know. The second group is the people that gifted to the museum, that although they were not here every day, they were closely involved with it, and they graced it with the fruits of their generosity. So I begin, of course, with my favorite, those who know me know that I am particularly keen on Georgiou Marfopoulos, who was the other original donor of the museum. The museum, when it opened in 1931, it had two collections, the Benaki family collections and the Georgiou Marfopoulos collection of Chinese art. But, of course, there is more. Eleni Stafatos, a great benefactress of several museums in Athens, and also someone who bequeathed treasures to the Benaki are Hellenistic jewellery, the beautiful Greek, early modern Greek art, and most important among the objects is, of course, the Kozani room. Damianos Kyriazis, much less known but a very important donor, who gave beautiful works of art and also everyday objects. And the Valladoros siblings here, Tasos and Maria, who bequeathed their home, which is now a small branch of the museum and a collection of Byzantine and post Byzantine Greek art. Apart from the collectors, we also had artists. And I am just mentioning here Nikos Chatzikyriakos Gika, who bequeathed his house, his studio, and gave his name to a whole branch of the museum, as was, of course, Yanis Papas, a great sculptor whose house and studio in Zografou is one of the most charming places you can visit in Athens and well worth every moment. So these were the people that although they didn't work every day in the museum, they gave gifts, which we all share today through the museum. So we have the people working here and the people who gave to the museum. And these people are preeminent in the mind of everyone who writes a guidebook. These people have to be commemorated. They have to be introduced. It's a better word than commemorated. Introduced to someone who wants to know more about the Benaki. But of course, then we have to introduce the buildings. We have to introduce the collections, what one can visit. Of course, we have the flagship Benaki Museum of Greek Culture. The Kika Gallery, which I've already referred to in Kolonaki. The Yanis Papas studio in Zografou. The Museum of Islamic Art in Keramikos. The Toy Museum in Faliron. Nima Pasmonteri, a small workshop in Petralona. The Valladoros Collection in Thession. The great Piraeus Kunsthalle, the exhibitions building in Petralona. And finally, the Patrick and John Lee Firm House in Kardamili, the only branch of the Benaki, which is outside Athens. So you can make a good tour of the city and a nice diversion to the Peloponnese. And you can enter, you can visit buildings from every architectural style and every stage of modern Greek architecture if you just visit Benaki museums. As members, you have free entry so you can visit all of them and you can imbibe the atmosphere of modern Greece through them. But in a guidebook, the author has really to focus on these buildings that have collections, that have objects in them. And the real challenge when you have to focus on less than 40 is how do you choose how many objects from each of these buildings that have collections. First, the lion's share goes to the Museum of Greek Culture, which has the most extensive representation, more than 6000 objects are included in the permanent display. I chose 16 out of them. The Giga Gallery got 5, the Giannis Papas Studio 2, the Valladoros Collection 1, 12 for the Benaki Museum of Islamic Art and 2 for the Toy Museum, a total of 38, out of which I chose to sort of discuss tonight with you 10. So it's not a top 10 really, it's just a selection of 10 that I think can keep us interested and not bore us too much on a Thursday evening. And these 10 fall into three categories. One is old hits and hidden treasures. Whenever you go into a museum, there are some objects you cannot possibly miss. These are the old hits. They are the poster boys, they are the objects that every newspaper will ask if it's going to write an article on the Benaki that every visitor to Athens will see on their app or on Google when they walk around the city. But also they are hidden treasures, they are objects that sometimes a guidebook has to pick out and tell their story. And this story will make them shine, even if they're not self-evidently very important. So that's part of our mission. Every object tells a story, but some stories are more exciting than others. The other category of objects are the objects that illustrate moments of transition and phenomena of interaction. The museum is wide ranging, and also it is spread across several buildings, as we saw. The collections are extremely varied. Greek art of all periods, Islamic art, but also they are in storage, Chinese art, Korean art, pre-Columbian American, and African art. Now, it is important at these times of isolationist narratives and of stronger and harder borders to actually stress how these things in the long run, in the historical long durée, never really applied. People have communicated for millennia, they have exchanged ideas, they have talked to each other, and they have created objects that show, that are transparent somehow within this cultural landscape. And the museum can pick out these objects and can show the connections across time, across geography, from one part of the world to the other. And finally, cosmopolitanism, which is, if you prefer, it's a much reviled word these days, and it's considered perhaps not very politically correct, but actually I would argue, and there is very good theoretical backing for that, there's a whole lovely book by Anthony Appiah, which I advise you to read, on the role of cosmopolitanism and how cosmopolitanism can teach us how to live with others. And when we often talk about people like Benaki and his ilk, we use this word, they were cosmopolitan. But at the time it meant that they were rich people that traveled the world, because then it was a privilege. Now, the world is in our doorstep. It's everywhere around us, so we'd better be cosmopolitans if we want to understand it. So, I will begin my top 10, which you shouldn't really see as top 10, with the old hits and hidden treasures. And this is undoubtedly an old hit. It is the Nobel Prize for Literature, the presentation folder of the Nobel Prize, given to Yorgos Seferis, the famous Greek poet, in 1963 by the Swedish Academy. It is a handsome leather folio with two leaves of parchment, actually in the catalogue it's incorrectly identified as paper, it's parchment. And it's inscribed to Yorgos Seferis for his poetry. This is a photograph from the ceremony. It was the first Nobel ever awarded to any Greek, so it was a huge honor for Greece. And it came at a golden time in Greek history, the early 60s, which was a time when the wounds of the war and the civil war were healing slowly. But Greece was becoming quite fashionable. There were great people at the time, internationally known, who were Greek and made Greece rather glamorous. So a Nobel suited this image very well. The beautiful illustration by a Swedish artist, who actually has illustrated all the Nobel Prizes for Literature since Bruşelic. This was the first one he painted, but he continued until the 80s, shows a Greek landscape and strong references to classical Greek art. So we see here a Nike statue, Dionysus on his boat, two very Minoan looking dolphins and a Greek temple, let's say like Sunion. However, Seferis in his speech, in his acceptance speech, he went another way. He didn't refer to ancient Greece. Actually, he said, and I have outlined it here, I have not spoken to you of the ancients. I did not want to tie you. Seferis didn't talk about classical Greece at all. He chose to talk about early modern Greece. So he referred to his heroes. He talked about Dominikos Tertokopoulos, El Greco. He talked about General Makrigiannis. He talked about Palamas. He referred to people that he saw as instrumental in creating the character of modern Greece. As a Greek poet of the 20th century, that was his duty to pay his homage not to the classical heritage, which belonged to the whole world, but to his very special Greek heritage, modern Greek heritage. And he talked also about that many faced expression, which is the Greek expression. And I think that is a wonderful way to open any guidebook on the Benaki. Now, the next object, number nine in the list, is definitely a hidden treasure. It lies at the basement of the Benaki Toy Museum in Phaliro, and it's made not of noble leather and parchment, but of cardboard and wood. And it was created by and for two children in Greece in the early 20th century. They were Marika Veloudiou and Thanos Veloudios, who also added to his name Mourais, Mourais of Mary, because he originated. Also, there was an English ancestor. Now, this is a model of a church, and for children, this would have been Hagia Sophia, the great cathedral of Constantinople. But of course, when we look at it, it doesn't look like Hagia Sophia at all. It looks like one of the charming Byzantine churches of Athens. The way of building, the plan of the church, the remarkable ceramic decoration on it. Even the ethnic dishes inlaid on the façade, the bacini on the façade, all that references Greek churches rather than Constantinopolitan. Now, the grandfather of Marika and Thanos was an archaeologist. So I believe it was the grandfather who took them with him on walks around the city they grew up in and showed them the churches. So they got inspired and they created this wonderful model, which they would have carried with them on the day before Christmas while singing the carols, as was the tradition in Athens at the time. Now, Marika and Thanos grew up to become quite individual people. She was the first Greek tourist guide and multilingual, charming. She was the guide for all the great and the good, but also pretty much everybody who wanted a good guide to take them throughout the antiquities of Greece and Athens especially. Thanos was a hero aviator. Famously, during the Asia Minor War, he landed at the courtyard of the Turkish Military Cadet School. He took down the Turkish flag and he raised the Greek flag and he flew off with his plane, which was remarkable. And then he went on to become an author, an actor, and the first and only Greek dadaist. So quite a figure. And he died at quite an old age. Now, the third object is another hidden treasure and is a particular favourite of mine because it was lying there on the third floor of the National Museum of Greek Culture. And everybody said, oh, it looks as if it's going to fall down any time soon. It's a huge porcelain vase, a crater. And it's painted with a portrait of a French soldier and politician, Eugene de Beauharnais. The reason it was exhibited at the museum was that by tradition this was given by the sitter, by Beauharnais, to Kapodistria, the first governor of Greece. And it was bequeathed by Eleni Kapodistria, a descendant of the governor, to the museum in 1951. However, we didn't know anything about it. Although there had been some efforts to research it, people thought that it was made in Seville in France because it was a French sitter. And why would it have been given by Beauharnais to Kapodistria and so on and so forth. And as I was looking through a book on German porcelain, I was lucky enough to find a dead ringer, an exact copy of that, a version of that vase, which is today in the National Museum of Bavaria in Munich. So I thought, let's research that. But that's very interesting. How did it end up in Munich? Now, Eugene de Beauharnais may not ring many bells as a name, but of course, his mother was the great Josephine de Beauharnais, who married, after Monsieur Beauharnais, who gave her the son, she married Napoleon Bonaparte, who would become the Emperor of France. So Eugene de Beauharnais was the adopted son of Napoleon. And he fought with Napoleon several wars. But after Napoleon's first defeat, he left Paris and the rather spectacular palace, the Hôtel de Beauharnais, the palace, the family palace in Paris, is today the residence of the German ambassador in France. And he got married to a rather beautiful German princess in Bavaria, who was the daughter of Maximilian I. Maximilian I was the king of Bavaria. So this French prince, so to say, ended up in Bavaria. And there he commissioned a series, I believe, of these vases, these impressive neoclassical portrait vases from the royal porcelain factory of Niffenburg, which is just outside Munich. And we do know that he had met Capodistria at the conference of Vienna after Napoleon's defeat. And Capodistria was instrumental in preventing something which people like Metternich, his arch nemesis and famous missaline, he was instrumental in preventing the split of France. In the Council of Vienna after the fall of Napoleon, there was a plan to separate France, to carve the country up in different regions, as happened with Germany after World War Two. And Capodistria fought for France to stay united. And I believe that Boarnet presented that crater to Capodistria as a Frenchman's token of gratitude for someone who supported his country. Now the date of manufacture of the porcelain is very telling to a Greek. It was made in 1821, the year the Greek Revolution began in Germany, in Niffenburg. We don't know exactly when it reached the hands of the governor, but we do know how the governor ended his life. He was assassinated in Nafplion and he was replaced by a king, and the young king was Otto of Bavaria, who was a nephew of Jean de Boarnet. So ironically, the story goes full circle. We have a German vase produced by a French prince in Bavaria and bequeathed to a Greek politician. And then the nephew of the French prince becomes the king of Greece. So we find that this object, which looks like a piece of decoration, a little bit of golden tatt, actually is tied in many, many ways into the history of the country of its eventual hosting. Now we go into a few objects that demonstrate transition and interaction. I would like to begin with object number seven, which again is not one of these very flashy gold or silver or painted objects. It's a comb for hair and it's sitting at the Museum of Greek Culture. Unfortunately, when you look at it, you can only see one side of the comb, but you really should be able to see both sides. One side on the left shows a female figure seated on a throne, holding a globe and a spear, and she's wearing a helmet, so she's very military looking. She's a personification of Rome, Roma. On the other side of the comb, there is another lady, she's not as military looking and she's holding a cornucopia and she's sitting under an arch. And she is Fortuna, good luck, and she's a personification of Constantinople. Now, amazingly, this comb shows the two great capitals of the Roman Empire, the old capital of Rome here and the new capital of Constantinople here. As an object, it is enigmatic for another reason. The shift from Rome to Constantinople happened in the fourth century. However, the comb is about two centuries later. It's probably sixth century, at about the time of Justinian. So why would someone remember this? Why would someone reference both capitals when the other capital, Rome, was kind of not a capital anymore? This is very good and very technical and very educational for us as Greeks to help us remember that what we call Byzantine was actually the continuation of the Roman Empire. And a lot of the institutions that continued in Byzantium well into the medieval period, long after the sixth century, even to the end, the 14th century and the 15th century when it collapsed, were institutions that had begun centuries before Constantinople became the capital in Rome. So an object having both capitals was an item of legitimization. It showed how the new capital took the institutions, the gravitas, the history, the kudos of the old capital. So this is an everyday object, arguably made of ivory, but a simple object which carries with it so much political weight. So we see one capital, the ancient one, and another one, the new one, pagan Rome, Christian Constantinople, both governed by emperors, both governed by the Senate, both having strong institutions of Mediterranean imperial power. And the object number six comes also from this wider late antique Roman world. It comes from Egypt, and it's a hanging, it's a textile, from a church. On the left we see a saint, Abu Makkaros, and to the right there is a woman, probably a deceased woman. She's dead, and they're praying together for her soul. We like to note the amazing arch above their heads, supported on two columns with capitals, and decorated with a checkered pattern. And also the attitude these people, the saint and the dead woman, are sitting in. They have raised hands in supplication, in prayer. This textile, remarkably preserved, was probably commissioned by the family of the deceased, and offered as a decoration to a monastic church in Egypt, where it was discovered. And the colors have survived admirably, as they do in Egypt. The second object in this series is another church textile, an ecclesiastical textile. It's about a thousand years younger. It dates from the later 17th century, from 1682. It is a silk, gold and silver thread epitaphios, a cloth which represents the deposition and the lament over the dead body of Christ. It's beautifully embroidered on blue silk, and it is amazingly signed by its maker, and we can see the signature at the extreme upper left hand corner, the Spinetas. Now the Spineta, we know a few things about her, was an embroiderer. She lived in Constantinople, the capital of the Ottoman Empire at the time. She was quite wealthy. We have records of the money she got for commissions, and she could easily be paid for a piece of textile like that, the equivalent of the income of a small village for a whole year. So she was a well-known, well-paid woman. She got commissions from Romania, commissions from Cyprus, so there was international fame assigned to her name. And if we compare that to the fate of women artists in Christian West at the time, I find it very surprising, because here we have a female representative of a religious minority in a Muslim capital and a woman. And she is successful. She bequeaths her fortune after her death, we have her will, and she is of course widely acknowledged as a great artist. However, the reason I have put this object here is not just its beauty or its wonderful history, but the fact that above the body of Christ, we have this baldachin, this dome supported on amazingly five columns, which I believe is four columns, but just for symmetry, an extra one has been added, which sort of frames the holy persons, Nicodemus, John, the two Marys, and gives gravitas and importance to the scene in an architectural setting. The next object is again an embroidery, but this time it is an embroidery not from a great enthusiastic artisan, but by an anonymous woman working in the island of Skyros, perhaps a century later. What she embroider is her diary. She may be a girl really in her teens in preparation for her wedding day. And what she's making is a cushion cover, a bolster cover. And what we see in this cushion is a wedding scene. There are various buildings. I believe that they look more or less like a monastery, and in the middle there's a church. So I believe that the two buildings on either side are probably cells, chapels, etc., but the one in the center is definitely more important, three domes across on top. There is a couple above it, and there is a musician playing music with them. We can almost hear the songs of the wedding ceremony. And I would like you to pay attention to the very schematic way that the holy buildings have been depicted. We have arches on columns, and some of them have checkered patterns, probably representing the paved floor of the building, and also hanging lamps from the different arches. So this was a kind of shorthand depiction of a church, of a holy space. The fourth object in this sequence is another piece of textile. I think that textiles are particularly important in the Benaki collection, and they are fragile survivals. They are interesting objects. They are very often outside the canon of art history. We usually deal with old paintings, frescoes, occasionally the odd piece of metal work or bronze or marble, but actually textiles were the soft and fragile gold of antiquity, the most valuable objects, and the objects of the highest technological advance in historical times. This time, this textile is in the Benaki Museum of Islamic Art. It's very small, about that big, and it's embroidered with a scene which must take place in a mosque. It must be a mosque in Egypt, since this textile dates from the 11th or 12th century, from the times of the Fatimid Caliphate in Egypt. What it shows, here you see a map, you see the Fatimid Caliphate, the purple expanse in North Africa, Syria, Lebanon, Jordan, and the Holy Land of Islam, and then you see in pink the Byzantine Empire above. So what we see in the detail is an arch supported on composite columns, an inscription on the arch in Arabic, which is very hard to read, and a man standing in front of the arch, his hands raised in prayer. When we put these four objects together, which are displayed not very close to each other, the 4th to 5th century Egyptian textile, the 11th-12th century Egyptian textile at another museum, the ecclesiastical textile from the first floor of the Museum of Greek Art, and also the fall cart cushion, we see in all four a sort of formulaic depiction, a sort of locus, a common ground for depicting holiness, divinity, as holy space, a place of prayer. The arch, the arch which stands between this world and the other world, an arch which is a mediator, a place of prayer, a place of communication with the divine. In some cases, the arch is almost a gateway, as it is in the case of the late antique Egyptian textile, where we have the saint and the mortal together. As it is in the case of the Islamic textile, where the ruler prays to God. And also, as we have it in the Despinetta epitaphios, where the holy figures are there in front of Christ, who has crossed the threshold of death, only we know full well to come back two days later. Now for the young girl embroidering her diary in Scyros in the 18th century, perhaps that's another threshold, not to the afterlife, but to the life after marriage. Finally, the last objects, cosmopolitanism. And I have singled out an object that probably most of you haven't noticed. It's half a bracelet made of silver with some gilding. It is situated in the Benaki Museum of Greek Culture in the small section where the big copy of the Hagia Sophia mosaic with the Virgin lies. It was made probably in Constantinople, sometimes in the 11th century, so about the same time as the Egyptian textile with the mosque scene. And it is decorated with a motif, which if you know your Arabic, you will recognize as Arabic letters. But of course, it's not very clear what they're saying. So it may be a version of Allah, God, but we can't be sure. Now in the 11th century, and we saw the map, you remember the map of the Byzantine Empire in pink and the Fatimid Caliphate in purple, the biggest power and the richest state in the Mediterranean had its capital in Cairo. And the relationship with Byzantium, with the Empire of Constantinople, ranged from animosity to peace and exchange and trade. The 11th century was a good time. There were quite a few relationships being built in the diplomatic level and in the economic level between the two states. And it's quite well known to students of Byzantine art that we can find evidence of this and of the use of Arabic letters on monuments in Greece and in Constantinople. And I'm just selecting here a monument that we can visit fairly easily. It is the monastery of Osius Lucas in Viotia, and you can see on the facades of the Panagia Church, of the Church of the Virgin, which dates from the turn of the millennium, about 1000. You can see here in brick, in laid brick, sort of pseudo-Arabic letters. They're called pseudo-Kuffik because they represent the so-called Kuffik style of Arabic writing. It's a sort of calligraphy. And similarly, we see these pseudo-Kuffik letters in bands of carved marble on the facade of the same church. But even if you go to Athenian churches and you look closely, you will see these Arabic looking letters up on the facades in various media. Sometimes they're clay tiles, sometimes they are cut tiles in mortar, sometimes they are carved marble. Did the people decorating the churches know what they were doing? Did they know that they were probably writing the name of Allah, the Muslim God, on their Christian church? Probably not. They were probably copying the decorative bands found on valuable textiles being exchanged between Cairo, the empire of the Fatimids, and Constantinople. These beautiful silks that would be luxury items and they would have these decorative bands, incomprehensible to a non-Arabic speaker and very attractive anyway. I mean, we can discuss for hours that, and there's a few people who have dealt with the inscriptions on the monuments, but very rarely do we find such an inscription on a small object, a piece of jewelry. So this is a very important item. My final item for tonight is a broken pot. So nothing glamorous, no silk, no silver or gold, no monumental marble. It consists of two shards of a dish made in ceramic in Syria sometime in the early 14th century. And it is painted, as most of us I'm sure recognize, with a scene of the descent from the cross, a scene we know full well from the Gospels and the version of which we saw at the Epitaphios of the Spinetta a little bit earlier. It's a scene which gets embedded into Byzantine iconography in the middle Byzantine period. Here I'm showing you the extraordinarily beautiful scene of the lamentation from Nerezi today in northern Macedonia, a fresco from 1164, one of the masterpieces of Byzantine art. But I invite you to look at the way the Virgin is embracing the body of that Christ and also to focus on the angels at the top end of the scene, flying, fluttering about and crying, lamenting the passing of Christ. And we can see similar angels at the top of this dish produced in Syria about 150 years later. Of course, those of you who know your Renaissance art will recognize similar angels and the beautiful Giotto frescoes in Italy in the Cavella Scrovegni. Here they are, sort of bodiless cherubims flying about, one of them bringing his sleeves up to his eyes, just like the cherubs in the Syrian dish. However, this dish produced somewhere around here on the map was not made to look only to the West. The iconography is Byzantine and we could call it correlated with later examples of Byzantine art. And I sort of made a fanciful connection with early Renaissance art in Italy. But it's also looking East. For example, the cloak of one of the Marys is dotted with these very characteristic three dots, which seem to be used to signify an expensive textile. We don't find them in textiles of the period, they only appear on textiles later in the Ottoman period. However, we can see here an Iranian dish made in the later 12th, early 13th century, which features a man wearing a similar textile, all decorated with triplets of dots. So this comes straight from an Iranian tradition of silk weaving. And also the faces of the people on the dish with the slanted eyes and the sort of coma shaped brows look very Mongol indeed, and I'm juxtaposing them here with an Ilhamid period dish from the 14th century. Finally, I would like to draw your attention to the little clouds surrounding the angels above the arms of the cross, these little scroll clouds, which are definitely coming from China. And I have here a 14th century vase from the museum collection, and you can see these sort of little scrolly clouds, which through Iran, they passed and became part of Islamic decorative vocabulary in the 13th and 14th century. So what we have here is a rather humble object, two pieces of a broken dish. Incidentally, there's two more pieces. One is in America and the other is in the Museum of Islamic Art in Cairo from the same dish. I fear they will never come all together. So we at the Benaki have two of them, and they show a Christian scene, which we may think is quite straightforward because Syria always had the big Christian population, but it's actually much more complicated. We have a Byzantine iconography, which spread west but also spread east. We have a lot of Iranian, Asian, but even Chinese ideas incorporated onto this object. And the object itself dates from one of the most fascinating times in the history of the Near East, the time of the Mongols, the time when Mongol princes were marrying Byzantine princesses. And they were raising rulers that were one day Buddhist, the next day Shiite Muslims, the next day Orthodox Christian, and they were even flirting with their old religion of animism at the same time. So this wonderful time of cosmopolitanism is reflected on this Syrian broken pot. What I tried to show in this, not top 10, but selection of 10 objects out of this very small book, which we hope will be on the bookshelves in about a year from now, if we can make it faster we will try, was how through a museum you can read history and culture in ways that go beyond the historical and beyond what we are taught at school. How we can have fun making connections and how we can educate ourselves further. I made the conscious choice when I undertook this contract, because I was prevented from using bibliography, to ask colleagues and friends to contribute to the entries. And I am acknowledging this at the bottom of the entries they have helped with by putting in their name. Interestingly, the editor of the series has told me that in 100 books they have produced from museums the world over. This is the first time that this has happened. I'm very glad. That's very benign. We do something for the first time, before many, many other museums. Because museum work, like scholarship, is not a solitary task. We share what we do, we all do it together. In the sense that you shared a bit of time with us tonight. And we thank you for this. And I hope you will join us soon when the museums will reopen in one of the Benakis. I will now stop sharing my screen and would be grateful if any of you have any questions you can post them on chat. I will wait for a few minutes, and I will read them. Silence for now. I don't know when it will be. Thank you. Yes. I don't know when it will be, if we can push it a little bit forward, but we thought we should share the news on this guidebook with members, friends and contemporaries first. Thank you. Okay, thanks are very good. Thank you. And any questions? Oh, yes, someone is asking, I showed a portrait of Kapodistria, the first governor of Greece. And they said, what's this portrait? Where is that portrait? And I didn't show it on accident. This portrait is the most beautiful portrait of any Greek I've ever seen. It's just majestic on oil painting. It was made by Thomas Lawrence, a great English portrait painter, and it hangs at Windsor Castle in England. And we tried to get the portrait to Athens for the great 1821 before and after exhibition, which will be ready in March at the Benaki Museum, the great celebration of the bicentenary of the Greek Revolution. We couldn't get the original, but we had the luck of getting a loan of an exact copy, an incredible facsimile, which will belong to us by the Rothschild Foundation for a few months for the exhibition. And if you want to see pretty much the portrait of Kapodistria by Lawrence, come to the exhibition from March, between March and November at the Benaki Museum. And, okay, thank you. Good. Oh, thank you. It's very nice to see congratulations and thanks. Good. I can't see any other questions. So I guess you can always come back with questions if you feel like writing an email. We will be waiting for you here. Σας ευχαριστώ πάρα πολύ. Thank you very much all. Thank you Nino for organizing things and thank you to Bonhams, our sponsors for this evening. Thank you Mr. McGuinness, it was wonderful. Hope we will be able to see all of you in a future webinar and stay safe and stay home. Thank you Mr. McGuinness again. Thank you very much.